Electricity consumption and RES plants in Greece: Typologies of regional units. (November 2018) - Kyriakopoulos, Grigorios L.; Arabatzis, Garyfallos; Tsialis, Panagiotis; Ioannou, Konstantinos
Abstract: In the study two typologies of regional units in Greece were developed that were based on their energy characteristics, such as electricity consumption in variable energy sectors–including the domestic, industrial, commercial, and agricultural– as well as the number and the respective installed power of renewable energy sources (RES) plants for electricity generation. These typologies' deployment aim at developing administrative tools that will draw the decision planning towards future energy policy in Greece. The statistical methodology adopted was a hierarchical cluster analysis. Particularly, two analyses were materialized, in line to the aforementioned energy characteristics. Under this methodological framework, the hierarchical cluster analysis resulted in four clusters, each featuring different characteristics. Specifically, in the first analysis the first cluster consists mainly of the lowest energy consumption regional units, while the fourth cluster consists mainly of the highest energy consumption regional units. Besides, the second and the third cluster consist of regional units where the RES penetration is significant, enabling the wider energy autonomy and independence from other, mainly fossil-fuelled, sources of energy production, whereas in the fourth cluster the participative role of RES in energy production was noted as very low. Highlights: Two typologies of Greek regional units upon energy features of domestic, industrial, commercial, agricultural interest. Decision planning of future energy policy in Greece, based on installed power of RES plants for electricity generation. Deployment of statistical methodologies that were based on four hierarchical clusters' analyses. Interpretation of statistical outcomes on RES penetration, in terms of energy autonomy and independence from fossil-fuels.